Commuting involution graphs for. Issue 9 (2nd September 2018) - Hart, Sarah; Sbeiti Clarke, Amal
ABSTRACT: In this article we consider commuting graphs of involution conjugacy classes in the affine Weyl group of typeC ̃ n . We show that where the graph is connected the diameter is at most n +2.